SYSTEMATIC REVIEW FAKTOR FAKTOR YANG DAPAT MENINGKATKAN KEMAMPUAN GURU BERPIKIR TINGKAT TINGGI - Mahatma, Mahatma; Supriyati, Yetti (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This study aims to identify what factors are a problem or a barrier for teachers to develop higher order thinking skills and what factors can improve teachers' higher order thinking skills. This research is a Systematic Review using the Preferred Reporting Items for Systematic Review and Meta Analyzes (PISMA) method. The results of the study identified several factors that hindered teachers from higher order thinking. With these results, it is hoped that teachers and related parties can focus on improving themselves on factors that can increase the ability of teachers to think at higher levels.